Anaerobic Propane Oxidation for Biological Sulphateand Thiosulphate Reductions - Diansyah, Gusti (UNIVERSITAS SRIWIJAYA, 2014)
The Ã‚Â existence Ã‚Â of Ã‚Â microbial Ã‚Â populations Ã‚Â that Ã‚Â use Ã‚Â short Ã‚Â chain Ã‚Â alkanes Ã‚Â (SCA) Ã‚Â (ethane, Ã‚Â propane Ã‚Â andÃ‚Â butane) as potential electron donors for the reduction of sulphate has been recently reported. The useof sulphur compounds in many chemical processing leads wastewaters containing high concentrationÃ‚Â of Ã‚Â sulphate Ã‚Â and Ã‚Â thiosulphate. Ã‚Â Batch Ã‚Â experiments Ã‚Â were Ã‚Â studied Ã‚Â to Ã‚Â determine Ã‚Â the Ã‚Â ability Ã‚Â of Ã‚Â mixedÃ‚Â sediment Ã‚Â cultures Ã‚Â from Ã‚Â Aarhus Ã‚Â and Ã‚Â EckernfÃƒÂ¶rde Ã‚Â Bay Ã‚Â to Ã‚Â anaerobically Ã‚Â reduce Ã‚Â sulphate Ã‚Â andÃ‚Â thiosulphate coupled to propane as electron donor. Ã‚Â In the presence of propane, sulphide productionÃ‚Â from Ã‚Â all Ã‚Â sulphate Ã‚Â and Ã‚Â thiosulphate Ã‚Â bottles Ã‚Â was Ã‚Â higher Ã‚Â than Ã‚Â the Ã‚Â sulphide Ã‚Â production Ã‚Â when Ã‚Â theÃ‚Â propane was not added.